ANALISIS PENDAPATAN ASLI DAERAH TERHADAP ANGGARAN PENDAPATAN DAN BELANJA DAERAH 2013 - Harinoto, Harinoto (Jurnal Ekonomi Modernisasi, 2015)
The research took place in the department of finance and asset management revenue Malang trying to analyze the potential of local financial resources that support local revenues, analyze the contribution of revenue to the budget, analyzing the constraints faced in optimizing Regional Revenue receipts, as well as efforts to overcome obstacles PAD is in optimizing revenues. The research uses descriptive-qualitative analysis approach intends to obtain in-depth study of the potential sources of finance and its implications Budget (budget). This type of research is descriptive who tried to describe in depth the object of research at the present time based on the facts as they appear. The results showed that the potential sources of local finance in the current budget year, local tax receipts increased, but revenues from levies fluctuate so that the necessary strategic efforts are more progressive, following receipt of Income Results of Regional Wealth Management The Separated also experienced improvement and other local Revenue valid from year to year fluctuations, in terms of the level of local autonomy based on the reception area, Malang still low, considering the contribution of local revenues to the budget by an average of 9117%, remaining at 90.18% contributed by sources other than those derived from the PAD, and there are still many obstacles faced in optimizing regional income, yet realistic in determining the revenue targets, are still high levels of leakage and breakouts, as well as reduced admission object types. Efforts to do is to strive for the determination of revenue targets made more realistic, eliminate leakage and break-out level, and strive for the type of object revenue from taxes and levies can be further improved